Environmental Impacts of Climate Change: A Comperehensive Review of Causes, Manifestations, and Solutions - Kreba, Sleem Ali (Journal of natural sciences, life and applied sciences, 2024)
Climate change is a pressing global issue that has garnered significant attention in recent years. The primarily causes of this change are human activities such as burning fossil fuels and deforestation, and has far-reaching impacts on the environment, affecting various aspects of our planet's ecosystems and natural resources. This review study focuses on addressing the significance and causes of the phenomenon and its impacts on the main environmental aspects including biota, water resources, air, and soil. Rising global temperatures results in melting polar ice caps and glaciers, leading to sea-level rise and coastal flooding. Changes in precipitation patterns contribute to more frequent and intense droughts, heatwaves, and storms, affecting ecosystems, agriculture, and water resources. Additionally, climate change disrupts natural habitats, leading to the loss of biodiversity and endangering numerous species. The increased concentration of greenhouse gases in the atmosphere also contributes to ocean acidification, negatively impacting marine life and coral reefs. These aspects of the phenomenon have clear impacts on the environmental aspects including biota, water, air, and soil. Addressing climate change and mitigating its impacts is crucial for the preservation of our environment and the well-being of future generations.
Keywords: Global warming; Greenhouse gases; Biodiversity; Soil; Water; Air